The importance of epistemological translations in the Global South - Efron, Laura (2021)
Over the centuries, the West imposed and sustained a dominant definition ofknowledge which asserted that Western knowledge is the only legitimateknowledge that was taught as part of the process of ?civilisation?, imposed in thecolonies. After centuries of independence, Latin American societies and postcolonial realities and ideas promoted the open debate of this historicalepistemological domination and enabled the circulation of other ideas coming fromthe peripheric world. In the Latin American context, these attempts to re-positionknowledge that was formerly marginalised from the mainstream are veryimportant and are still taking place, as the dominating universals were notcompletely destroyed yet. Based on a theoretical review, the aim of this article isto underline the importance of epistemological translations as they enable ahorizontal dialogue among different systems of knowledge, and also promote theproduction of new ideas from the margins. More importantly, based on a literaturereview, this article introduces the idea of translation as a tool that promotes thedemocratisation of knowledge from the margins and shares Zapatista?s case toreflect on that.